2018
DOI: 10.1530/rep-18-0051
|View full text |Cite
|
Sign up to set email alerts
|

Imprint stability and plasticity during development

Abstract: There have been a number of recent insights in the area of genomic imprinting, the phenomenon whereby one of two autosomal alleles is selected for expression based on the parent of origin. This is due in part to a proliferation of new techniques for interrogating the genome that are leading researchers working on organisms other than mouse and human, where imprinting has been most studied, to become interested in looking for potential imprinting effects. Here, we recap what is known about the importance of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 113 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Some imprinted genes exhibit tissue-specific imprinted expression (8,(45)(46)(47). Cobl at the Grb10 imprinted region was reported to be only imprinted in mouse yolk sac and we found it was biallelic in mouse embryos (SI Appendix, Fig.…”
Section: Loss Of Zfp57mentioning
confidence: 72%
See 1 more Smart Citation
“…Some imprinted genes exhibit tissue-specific imprinted expression (8,(45)(46)(47). Cobl at the Grb10 imprinted region was reported to be only imprinted in mouse yolk sac and we found it was biallelic in mouse embryos (SI Appendix, Fig.…”
Section: Loss Of Zfp57mentioning
confidence: 72%
“…To date there are about 150 known imprinted genes, with more than half of them conserved between mice and humans (1,3). It is well established that genomic imprinting is required for mammalian sexual reproduction and embryonic development (1,(8)(9)(10). Loss of genomic imprinting causes many human diseases, such as diabetes, cancer, and neurological disorders (11).…”
mentioning
confidence: 99%
“…Uncovering a DMR at a region controlling ZFP57 transcription as the top hit in an unbiased screen was particularly striking in the EpiFASSTT randomized controlled trial, where we have already shown, using a candidate gene approach, that methylation levels were perturbed at some imprinted loci. The primary importance of ZFP57, as described in the literature from mechanistic work, is in maintaining imprinting, and it is currently the only protein known to be dedicated solely or largely to this epigenetic process [53]. ZFP57 was discovered as a maternal-zygotic effect gene which was required in mice for establishing methylation at some imprints in the oocyte, and for maintaining all imprints, both maternal and paternal, in the preimplantation embryo [38].…”
Section: Discussionmentioning
confidence: 99%
“…The murine ERVK family drives non-canonical, histone-dependent imprinting in the extraembryonic lineage [ 61 ]. Imprinted loci are established during epigenetic reprogramming of the germline and persist in the early embryo [ 54 , 62 , 63 ]. In contrast to epialleles, heterochromatin induction at imprinted loci is not stochastic but established at either the paternal or maternal allele, respectively, and is essential for proper development.…”
Section: Epigenetic Reprogramming Of Ervsmentioning
confidence: 99%